ANALISIS DATA PENILAIAN KINERJA GURU MENGGUNAKAN MANY FACET RASCH MEASUREMENT (MFRM) - sugiarto, sugiarto (Jurnal Penelitian dan Penilaian Pendidikan, 2024)
Many Facet Rasch Measurement (MFRM) is a measurement method in modern test theory that produceslinear and objective measurements. This paper offers the use of the MFRM method in TeacherPerformance Assessment (PKG) to analyze data on simulated assessments by the principal and 2 fellowteachers. In the context of PKG in schools, the judging plan can be made complete so that there is linkageof all the elements involved in the measurement.